Urgensi Pendidikan Agama Islam di Era Globalisasi - Nasiri Nasiri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2020)
Abstract: This research is a library research with a qualitative approach. Data collection techniques in this study are using documentary techniques, while the method used is content analysis and interpretation. This study aims to determine the urgency of Islamic religious education in the era of globalization, and as a result of this research is the importance of Islamic religious education in the era of globalization is as a foundation to minimize moral degradation and create human resources that have moral values, Islamic religious education solutions to moral degradation because Islamic religious education aims to shape people who have morality and prepare competent human beings by mastering religious knowledge and knowledge. Keywords: Urgency, Islamic Religious Education, Globalization